2020
DOI: 10.1002/ehf2.12578
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic prognostication of left ventricular hypertrophy and three‐dimensional mechanical dyssynchrony in heart failure

Abstract: Aims In this study, we investigated the prognostic interplay of left ventricular hypertrophy and mechanical dyssynchrony (LVMD), both of which can be measured three‐dimensionally by gated myocardial perfusion imaging (MPI), in patients with chronic systolic heart failure (HF). Methods and results In 829 consecutive HF patients with reduced left ventricular ejection fraction less than 50%, LVMD was evaluated as a standard deviation (phase SD) of regional onset of mechanical contraction phase angles. A phase his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…LVMD and left ventricular mass index (LVMI) as an index of LVH were evaluated using three-dimensional data derived from resting myocardial perfusion imaging (MPI) with 99m Tc-tetrofosmin of 300 MBq, as shown by our previous study ( Figure 1 ) [ 11 , 12 , 13 ]. Briefly, MPI SPECT was performed using an ECG-gated approach with a frame rate of 16 and a single-head gamma camera equipped with a high-resolution, parallel-hole collimator.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…LVMD and left ventricular mass index (LVMI) as an index of LVH were evaluated using three-dimensional data derived from resting myocardial perfusion imaging (MPI) with 99m Tc-tetrofosmin of 300 MBq, as shown by our previous study ( Figure 1 ) [ 11 , 12 , 13 ]. Briefly, MPI SPECT was performed using an ECG-gated approach with a frame rate of 16 and a single-head gamma camera equipped with a high-resolution, parallel-hole collimator.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, MPI SPECT was performed using an ECG-gated approach with a frame rate of 16 and a single-head gamma camera equipped with a high-resolution, parallel-hole collimator. LVMD and LVMI were measured using three-dimensionally reconstructed ECG-gated data of serial 10- to 14-short-axis SPECT images with the Heart Function View software (HFV version 1.1;Nihon MediPhysics, Tokyo, Japan) [ 12 , 13 ] and Corridor 4DM version 6.0 software (INVIA Medical Imaging Solutions, Ann Arbor, MI, USA) [ 11 ], respectively. LVMD was quantified as a standard deviation (SD) of phase angles (degrees) on a phase histogram ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In the study by Doi et al, left ventricular mechanical dyssynchrony was assessed as standard deviation on a phase histogram calculated by Fourier phase analysis applied to three-dimensionally obtained regional time-activity curves. 11 Three-dimensional left ventricular mechanical dyssynchrony assessed by gated-SPECT was previously shown to be a reliable and reproducible variable, 14,15 and to improve the prognostic stratification of heart failure patients when used in combination with clinical variables 14 and cardiac sympathetic nerve activity assessment. 15 The results of the study by Doi et al 11 extend while confirming previous findings suggesting that three-dimensional left ventricular mechanical dyssynchrony assessed by gated-SPECT may be an independent predictor of lethal cardiac events in heart failure patients.…”
mentioning
confidence: 99%
“…15 The results of the study by Doi et al 11 extend while confirming previous findings suggesting that three-dimensional left ventricular mechanical dyssynchrony assessed by gated-SPECT may be an independent predictor of lethal cardiac events in heart failure patients. 14,15 The specific contribution of the study is that three-dimensional left ventricular mechanical dyssynchrony may further discriminate heart failure patients with mid-range to severe grades of QRS prolongation and systolic dysfunction, thus improving the prognostic assessment of such patients. Accordingly, in a previous study left ventricular mechanical dyssynchrony by phase analysis of gated-SPECT was shown to be an independent predictor of all-cause mortality in patients with non-ischemic cardiomyopathy, ejection fraction 35%-50%, and QRS duration\150 ms. 16 Furthermore, the results of the study by Doi et al 11 reflect the possibility that QRS duration may not be a parameter directly related to the presence of left ventricular dyssynchrony and therefore to the response to Cardiac Resynchronization Therapy, especially in the absence of left bundle branch block.…”
mentioning
confidence: 99%